Life cycles of chromerids resemble those of colpodellids and apicomplexan parasites - Oborník, Miroslav; Kručinská, Jitka; Esson, Heather (Schweizerbart Science Publishers, 2016)
Chromerids are alveolate algae with secondary plastids surrounded by four membranes, and with evolutionary positions close to the root of apicomplexan parasites. As both described chromerid species, Chromera velia and Vitrella brassicaformis, are, in spite of their phototrophy, distant relatives, there are some differences between their respective life cycles. Here, we summarize current knowledge of the life cycles of chromerid algae and the related colpodellids. We also describe zoosporangia formation and excystation in C. velia. We suggest that the formation of zoospores in C. velia is homologous to schizogony in apicomplexan parasites
Keywords: Life; cycles; chromerids; resemble; colpodellids; apicomplexan; parasites